Teknologi Informasi dan Kualitas Laporan Keuangan UMKM - Teguh Erawati; Safira Nurul Fajriati (Ekonomis: Journal of Economics and Business, 2023)
This study aims to examine and prove the influence of perceptions of the purpose of financial statements, accounting knowledge, and Information Technology on the quality of MSME financial statements. The population in this study is UMKM actors Pandeyan Kemantren Umbulharjo Yogyakarta who already have NIB (Induk Berusaha number) / IUM (Micro Business License). This research is quantitative with a  purposive sampling technique. The results of this study indicate that there is a positive influence between the perception of the purpose of financial statements, accounting knowledge, and Information Technology on the quality of MSME financial statements.